O agir didático do professor de Língua Portuguesa e sua reconfiguração em textos de autoconfrontação - Silva, Carla Messias Ribeiro da (2013)
This research aims to characterize the didactic act of two female teachers of Portuguese during 2 teaching practices about 2 textual genres from the narration axis, namely, comics and short story, and verify the reconfiguration of this act by the teachers themselves in texts with simple and crossed self-confrontation. We understand as didactic act teachers interventions when interacting with students in the process of turning a teaching object into an effectively taught object. This thesis inscribes itself in the current movement of researches on the Portuguese teacher s job, which, by means of empirical studies, aims to contribute to broadening the Portuguese teacher s perception of her/his own act in the classroom. Thus, this thesis in Applied Linguistics is inscribed, in a basilar and triangular way, into the theoretical approach of sociodiscursive interactionism and contributions from the Didactics of Languages and the Clinic of Activity, in order to seek answers to analyze teachers' job, by crossing 2 methods that we regard as complementary to practice the métier, and the Portuguese teacher her/himself: the analysis of practice by an external observer (the researcher) and by teachers participating in the research. Regarding the method to generate data, we used the self-confrontation device (CLOT, 2010): audio and video recording of classes and simple and crossed selfconfrontations. We organized the analytical method in two steps: 1) analysis of teaching practices: the object of teaching, school activities, tools, and didactic devices, social forms of work, and the fundamental and specific didactic gestures (SCHNEUWLY; DOLZ, 2009); and 2) analysis of self-confrontations (MACHADO; BRONCKART, 2009; BULEA, 2010). With the results of analysis, we could characterize the didactic act of both female teachers with regard to the textual genres and the reading practices, in addition to observations by teachers themselves about their work and act. Thus, we identify the reading practices that are secularized in the Portuguese teacher s job, extend the notion of didactic gestures, and found out that the method adopted in this thesis may constitute the first step of a continued education based on concrete classroom situations